Zakat calculation system for Academy of Contemporary Islamic Studies (ACIS), UiTM Melaka Campus Jasin / Nurshafinas Muhammad - Muhammad, Nurshafinas (2017)
Universiti Teknologi Mara (UiTM) is a public university and one of the largest higher education institution in Malaysia in terms of size and population. UiTM is the only university in Malaysia that has campuses in every state of the country and one of the campus is UiTM Melaka Campus Jasin. In UiTM management, there are many different departments for different matters. One of the department is Academy of Contemporary Islamic Studies (ACIS) which manage everything related to Islamic matters. The project will be focusing on Zakat matters which including manage and distributing the Zakat to the students who are eligible to receive the Zakat. To avoid redundant data and loss of information, ACIS department needs a web-based system that can record all the student’s information and student’s parent income details which required by the ACIS in more organized, systematic and easy to retrieve. The system also needs an accurate automatic calculator in calculating the ‘Had Kifayah’ so that it can determine the students is under which Asnaf category. This project is carried out with an aim to develop the Online Zakat Calculation System using the conditional control statement technique and waterfall model is used as methodology. Only four phases of waterfall model were applied in this project which are requirements gathering, requirements analysis, design and implementation. As a result of this project, an Online Zakat Calculation System for Academy of Contemporary Islamic Studies (ACIS), UiTM Melaka Campus Jasin is produced together with documentation of Software Requirements Specification (SRS) and Software Design Document (SDD). As recommendation for future work, this project may enhance by other researcher who interested to improve this project into mobile application platform or other suitable features enhancement to maintain the acceptability of this project due to evolving of technology.